2015
DOI: 10.5455/aim.2015.23.12-17
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Cost Index and Comfort Walking Speed in Two Level Lower Limb Amputees Having No Vascular Disease

Abstract: Background:The Physiological Cost Index (PCI) was introduced by MacGregor to estimate the energy cost in walking of healthy people, also it has been reported for persons with lower limb amputation, walking with prosthesis.Objective:To assess energy cost and walking speed in two level lower limb amputation: transfemoral and transtibial amputation and to determine if the age and prosthetic walking supported with walking aids have impact on energy cost and walking speed.Methods:A prospective cross sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
0
14
1
Order By: Relevance
“…Given the fact that more than 50 studies were identified, studies with a sample size less of than 10 participants were excluded (n = 27). Two studies were found [ 36 , 37 ] that partially included the same study population (in one study persons with a Syme amputation were included and in the other study they were excluded). The former study was included in this study [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the fact that more than 50 studies were identified, studies with a sample size less of than 10 participants were excluded (n = 27). Two studies were found [ 36 , 37 ] that partially included the same study population (in one study persons with a Syme amputation were included and in the other study they were excluded). The former study was included in this study [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were found [ 36 , 37 ] that partially included the same study population (in one study persons with a Syme amputation were included and in the other study they were excluded). The former study was included in this study [ 36 ]. In total 61 studies were included.…”
Section: Resultsmentioning
confidence: 99%
“…Mengelkoch et al 10) demonstrated that the energy cost and performance of below-knee amputees was disadvantageous during walking and running activities compared to non-amputee runners. Furthermore, it is known that the energy cost of physical activities is higher in above-knee amputees compared with below-knee amputees 11) . From these factors, it can be assumed that the energy cost of physical activities is higher in the amputation group compared with the non-disabled group.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the limited number of prosthetic users available for this study, we performed a prior power analysis to identify the minimum sample size necessary to yield results of sufficient power and confidence for the known-groups construct validity assessment. The power analysis was conducted based on values for walking speed (no walking aid) from persons with transfemoral amputation and transtibial amputation [38]. The mean walking speed (SD) was: 65.64 m min -1 (4.18) and 79.02 m min -1 (11.26) for persons with transfemoral amputation and transtibial amputation, respectively, with an estimated difference of 13.4 m min -1 between the groups.…”
Section: Methodsmentioning
confidence: 99%